2021
DOI: 10.37766/inplasy2021.8.0062
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effects of four exercise modalities in nonalcoholic fatty liver disease:systematic review and Bayesian network meta-analysis

Abstract: Sensitivity analysis: Not applicable. A metaanalysis will not be performed. Language: English. Country(ies) involved: China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…Our study found that AT + RT is the best for overall improvement of TC and TG in NAFLD patients. The results are consistent with previous studies [75]. For ALT and AST, we found that the best way to improve their exercise is AT and RT, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that AT + RT is the best for overall improvement of TC and TG in NAFLD patients. The results are consistent with previous studies [75]. For ALT and AST, we found that the best way to improve their exercise is AT and RT, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Previous large systematic reviews, including a recent Cochrane review and those with quantitative meta-analysis, have examined the individual components of the ACSM FITT exercise prescription, including frequency, intensity, time, and type. 47 , 57 , 107 , 130 Each has found significant heterogeneity owing to variation in the FITT principles. Across the primary literature, exercise frequency ranges from 3 to 7 days/wk; intensities that have been studied include low, moderate, moderate-vigorous, and vigorous.…”
Section: Considerations For Prescribing An Exercise Training Programmentioning
confidence: 99%
“…Exercise interventions have been demonstrated to significantly improve the liver transaminases regardless of the age, although more profound benefits have been observed in younger adults[ 30 ]. Along with improvements in MAFLD, various exercise programs have also been associated with improvements in metabolic parameters such as plasma levels of glucose, insulin, HbA1c, LDL-C, triglycerides, and HOMA-IR[ 31 , 32 ].…”
Section: Management Approach To Mafldmentioning
confidence: 99%